(3GdCSGS aj Yde GdEbJUGO (B/s - (3GdhGOj, eMehOs; (3NQjS, GHQGgjes ((3YeGf(B: s (3OGQ GdjGRhQj GdYdejI(B, s, 2007)
(3jVe eONd YGe ddEbJUGO, YfGUQ GdEfJGL hfXQjI GdWdH, JMOjO GdCKeGf, GdShb , GdESJgdGc hGdESJKeGQ, GdONd Gdbhej hGdfGJL Gdbhej, GdCLhQ hGdHWGdI hGdJVNe , GdSjGSI GdfbOjI hGdeGdjI , dfbhO hGdHfhc , GdJLGQI GdNGQLjI hGdJfejI GdEbJUGOjI(B. s
(3HjHdjhZQGajG(B: (3U(B.335 ((3EbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdESJKeGQs; (3GdESJgdGcs; (3GdEfJGLs; (3GdShbs; (3Yde GdGbJUGOs